The Three in One and One in Three: Changing Relations Between Centre and Field in the NHS - Dopson, S; Locock, L (1999)
This article examines the changing nature of the central organization of the NHS and its relations with the field. It is based on a two-year tracer study of regional health authorities (RHAs) as they were reorganized into regional offices (ROs) and became part of the civil service. The research evidence suggests that the centre of the NHS cannot be treated as one organization; the wider Department of Health, NHS Executive HQ and regional offices have distinct identities within it. The analysis therefore looks at relations between these different components of the centre, and between them and the field. The significance of the recent White Paper for the future of regional offices is discussed, with particular emphasis on the tension between centralization and decentralization in performance management, and the opportunity to rebuild strategic co-ordination, which has been difficult to maintain under the internal market.